Peran Penyuluh dalam Memotivasi Petani dalam Berusahatani Cabai di Desa Guwang, Kecamatan Sukawati, Gianyar - NI LUH AYU PURNAMANING SANDHI; I GEDE SETIAWAN ADI PUTRA; NI WAYAN SRI ASTITI (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2020)
The Role of Extension Agents in Motivating Farmers in Chili Farming Cooperation between extension workers and farmers is needed to produce good and quality farmers. Therefore, the instructor acts as a facilitator, guide, communicator and motivator in order to motivate farmers in the chilli business. With the extension, it is hoped that chilli farmers in Guwang Village, Sukawati District, Gianyar can increase the productivity of their chili farming. The research aims to determine the role of instructors as facilitators, mentors, communicators and motivators. Locations were determined using the deliberate method with a qualitative quantitative descriptive analysis method. The results of the study and discussion that the role of instructors as facilitators, mentors, communicators and motivators are categorized very well. The role of the instructor as a facilitator in motivating farmers in the chilli business gained a good category. The role of extension workers in Guwang Village, is included in the excellent category. The instructor should provide guidance not only on how to cultivate the chillies properly but also provide guidance on how to use the tools correctly and clearly. The instructor must also pay more attention to the materials and innovations provided to local farmers, so that all farmers in Guwang Village want to be actively involved in the extension activities.